Open constitution and powers of Parliament. Commentary on Constitutional Court ruling 137/2025, of june 26, on the amnesty law - Tajadura Tejada, Javier (Journal of the Basque Parliament, 2025)
The approval of Organic Law 1/2024, of June 10, on amnesty for the institutional, political, and social normalization of Catalonia, immediately raised many doubts about its constitutionality. Constitutional Court Ruling 137/2025 declared it constitutional. This paper criticizes this ruling, arguing that it endorses a constitutional amendment without following the reform procedure, as denounced by the dissenting justices. The Court's response –which contradicts the wording of Article 66 of the Spanish Constitution, the regulation of the right of pardon in Article 62, and the constitutional debates– I consider erroneous. Even assuming that granting amnesty had been a politically and socially peaceful matter, from a strictly legal-constitutional perspective, there are very strong arguments to support the claim that the Spanish Parliament does not have the power to grant amnesties.
Keywords: amnesty; right of pardon; parliamentary sovereignty; normative constitution